Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - 2.2 - Addition and Subtraction of Rational Numbers - Problem Set 2.2 - Page 58: 85



Work Step by Step

We first apply the distributive property. Then, we simplify the resultant expression: $\frac{1}{2}x+\frac{2}{3}x+\frac{1}{6}x$ =$x(\frac{1}{2}+\frac{2}{3}+\frac{1}{6})$ =$x(\frac{1(3)+2(2)+1(1)}{6})$ =$x(\frac{3+4+1}{6})$ =$x(\frac{8}{6})$ =$x(\frac{4}{3})$ =$\frac{4}{3}x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.